Nexus between Non-Oil Sectoral Contribution and Economic Growth in Nigeria 1981-2018 - Usoro, Akanimo Ernest; Yusuf, Wasiu Akintunde; Okafor, Bartholomew O. N (The Economics and Finance Letters, 2020)
Nigeria has the largest economy in Africa and has the potential of rising through the world rankings to be among the top economies in the world. To achieve this however, diversification from over dependence on crude oil is required. Nigeria’s intrinsic potential lies beyond oil; harnessing this potential has become an imperative given the volatility of oil prices. This study identifies the non-oil sector as a priority sector with the most dominant transmission links to the overall economy. This sector in the medium-to-long term is key to boosting employment, reducing poverty and improving domestic food security. Therefore, the nexus between non-oil sector contribution and Nigeria economic growth is investigated, vis-a-vis the effect of government’s increased focus and investment in this sector. The study employed Autoregressive Distributed Lag (ARDL) model and Vector Error Correction Model (VECM). The reason for using this model is that it is simple and can be applied easily without consideration for the stationarity of the variables (at level or at first difference). The results confirmed the short-run relationship between the variables where non-oil revenue immediately impact the GDP growth of Nigeria by 8.49%. The study then conclude that the non-oil sector is crucial to the economic growth of Nigeria and therefore suggested increased government investment in the non-oil sector as well as strengthening of institutions.